Cloning DNA sequences from influenza viral RNA segments. - Lai, C J (1980)
DNA sequences corresponding to gene segments that code for the nonstructural protein, the matrix protein, and the hemagglutinin of influenza A virus [strain A/Udorn/72 (H3N2)] were cloned in Escherichia coli pBR 322. Initially, positive and negative cDNA strands were prepared separately by reverse transcription. The positive strands of cDNA were transcribed from genomic RNA segments by using a specific dodecamer DNA sequence as a primer; the negative strands of cDNA were transcribed from cytoplasmic viral mRNA segments by using an oligo(dT) primer. DNA duplexes corresponding in size to the virus RNA segments were then purified, inserted into the plasmid DNA, and used for transformation of E. coli. The influenza virus-specific DNA sequences isolated from recombinant plasmid molecules were characterized by mapping restriction enzyme cleavage sites. In addition, the orientation of cloned DNA was determined with reference to the 3' terminus of viral RNA.